Physical activity experience of patients with hypertension: a systematic review and synthesis of qualitative literature - Qun Li; Jieqiong Jiang; Anyan Duan; Jiao Hu; Ling Li; Wei Chen (BMC Public Health)
Abstract Background Hypertension continues to increase in prevalence, and it has become a major cause of increased mortality globally. Physical activity (PA) has been shown to be a first-line treatment for controlling blood pressure. However, participation rates in PA are still poor. Therefore, it’s imperative to explore the factors that affect patient PA adherence. Methods A synthesis of qualitative research of the PA experience of patients with hypertension was conducted. We systematically searched for qualitative studies published in English from inception to May 2023 in the databases of PubMed, Embase, Web of Science, CINAHL, PsycINFO, and Cochrane Library. The Joanna Briggs Institute tool was used to extract data, and the Capability, Opportunity, Motivation-Behaviour model was used to synthesize data. Results This qualitative research included 17 studies, identified 85 findings, summarized 9 categories, and finally meta-aggregated 3 synthesized findings, including capabilities of patients with hypertension, PA opportunities and PA motivators. The capabilities included age, other health problems, and PA knowledge and skills. Opportunities included time constraints, environmental factors, physical activity resources, and social support. Motivators included self-efficacy, pursuing physical health, and experience from PA. Conclusion The available evidence contributes to a comprehensive understanding of the barriers and facilitators of PA in patients with hypertension. Most of these barriers can be addressed and improved. When designing and implementing physical activity programs for patients with hypertension, an individualized PA program should first be designed, tailored to the patient’s capacity. Secondly, patients should be provided with additional PA resources and enhanced social support. Lastly, patients’ motivation can be increased by enhancing their PA experience.